TRANSFORMASI MODEL INOVATIF UNTUK PELAYANAN TERPADU SATU PINTU (PTSP) DI INDONESIA - Muhammad Khoirul Anwar (Universitas Muhammadiyah Jakarta, 2017)
Act No. 25 of 2009 on the Ministry of the public have been enacted in July 2009, seven years ago, however the betterment of public service seems still far from the goal of Act 25/2009. An example of the bad conditions of Indonesian public services is that illegal charges on public service organizer are still frequently found, hence President issued a Regulation 87 2016 about SATGAS SABER PUNGLI (task force to eradicate extortion). One Stop Service (OSS/PTSP) offers different things. According to a survey conducted by ORI on 2015, the results showed that amongst all 26 of the OSS (PTSP) only 2 of them are getting low compliance, 15 medium compliance, whilst 9 of them achieve excellent compliance. Likewise, compliance of Sub-Urban PTSP, from surveyed 57 PTSP only 14 PTSP get low compliance, 34 medium and 9 excel- lent compliance. In Urban PTSP, from surveyed 46 PTSP who only 8 BPTSP get low compliance, 19 medium, and 19 excellent compliance. This shows that the PTSP is much more obedient and is certainly ready to transform towards the attainment of a higher quality service. Referring to the proposals of Team of Deputies Administration Innovation of State Administrative Agency, with regards to survey results carried out by Ombudsman RI in 2015, PTSP included in red zones is transformed into reinforcement model, PTSP included in yellow zone is transformed into a accelerated model and PTSP included green zone is transformed into innovative models. The effectiveness of the transformation of the PTSP is proved to be very dependant to Commander within areas, as shown by the case in the East Java and South Sulawesi provinces, and cities and Regencies which regions Commanders have strong commitment, then the PTSP can change quickly and are able to initiate changes specifically for the creation of a conducive business climate. Hence, the local government should form a special Team involving the entire stake holders, including the characters, user services and academia so that the results is considered with regards of needs and relevant challenges.Keywords: OSS (PTSP), The complaint, Pungli, Compliance, Model Of Reinforcement, The Acceleration Model, A model of innovation